2004
DOI: 10.1016/s1352-2310(04)00369-3
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of aqueous oxalic acid production in the coastal marine atmosphere

Abstract: Oxalic acid is the most abundant dicarboxylic acid found in the troposphere, yet there is still no scientific consensus concerning its origins or formation process. Recent studies have suggested mechanisms for its formation in cloud water from gaseous precursors. Comparison of the characteristics of oxalic acid and nss sulfate, a chemical with a known incloud formation pathway, provides some support for an aqueous formation mechanism for oxalic acid. Analysis of the filters collected from the CIRPAS Twin Otter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 3 publications
1
36
1
Order By: Relevance
“…Between one to six cloudwater samples of approximately 10−30 min duration were collected each flight, which typically lasted ∼4−4.5 h. Samples were obtained with a modified Mohnen slotted-rod cloudwater collector. 26,45,52 The collection efficiency of the collector increases with decreasing aircraft speed and has little correlation with drop diameter up to a mass mean diameter of approximately 35 μm; 53 the range of drop sizes encountered during E-PEACE are expected to have been sampled by the collector with variable size-dependent collection efficiencies. The drop-size dependent sampling efficiency and possible large drop shatter might bias the concentrations of metals, organics, and other solutes since their concentrations change with drop size (e.g., refs 54−57).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Between one to six cloudwater samples of approximately 10−30 min duration were collected each flight, which typically lasted ∼4−4.5 h. Samples were obtained with a modified Mohnen slotted-rod cloudwater collector. 26,45,52 The collection efficiency of the collector increases with decreasing aircraft speed and has little correlation with drop diameter up to a mass mean diameter of approximately 35 μm; 53 the range of drop sizes encountered during E-PEACE are expected to have been sampled by the collector with variable size-dependent collection efficiencies. The drop-size dependent sampling efficiency and possible large drop shatter might bias the concentrations of metals, organics, and other solutes since their concentrations change with drop size (e.g., refs 54−57).…”
Section: Methodsmentioning
confidence: 99%
“…INTERACTIONS IN STUDY REGION Oxalic acid can form metal complexes in the marine boundary layer due to the ubiquity of metals in directly emitted particle types (e.g., sea salt, dust, fly ash), the ubiquity of oxalate in aerosol particles in the study region, 26,36,69 and the favorable aqueous-phase medium provided by cloud drops to promote efficient complexation between metal and oxalate ions. 83 While we only considered complexation of iron by oxalate, other organic ligands (acids, humic like substances) might also form iron complexes.…”
Section: Implications Of Oxalate-metalmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a number of field studies have shown that the high amount of non volatile organic acids (such as oxalic, malonic, malic, succinic, glutaric acids) found in atmospheric waters and aerosols originate from aqueous phase processes Yao et al 2003;Crahan et al 2004;Yu et al 2005;Sorooshian et al 2007). These observations were in good agreement with the fact that, in the aqueous phase, the atmospheric reactivity is different from the gas phase one, leading to the formation of less volatile products.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%